Prevalence of chloroquine-resistant falciparum malaria in the Brazilian Amazon - Ferraroni, JoséJ J.; Speer, Clarence A.; Hayes, J.; Suzuki, Mamoru (American Journal of Tropical Medicine and Hygiene, 1981)
The prevalence of chloroquine-resistant falciparum malaria was determined for humans living at 28 different sites in the Brazilian Amazon. Blood samples obtained from each patient were defibrinated, placed in vials containing 0.5% glucose and or chloroquine and incubated for 24 hours at 39-40°C without agitation. In vitro sensitivity of the parasite to four different concentrations of chloroquine was determined for each sample. After 24 hours of incubation, trophozoites of Plasmodium falciparum developed to schizonts in all control cultures (no chloroquine) as well as in 80.6, 48.4, 11.8 and 7.5% of the cultures containing 0.5, 1.0, 2.0, and 3.0 nmol chloroquine/ml blood, respectively. Chloroquine-resistant P. falciparum was found in blood samples from all 28 locations, indicating that such resistance is widely spread in the Brazilian Amazon.
Keywords: Chloroquine; Animals Experiment; Drug Resistance; Drug Response; Epidemiology; Geographic Distribution; In Vitro Study; Malaria; Plasmodium Falciparum; Protozoon; Animalsia; Plasmodium Falciparum; Protozoa